Pengaruh Penambahan Bubuk Coklat terhadap Sifat Fisik, Kimia, dan Organoleptik Minuman Instan Bekatul - Hadi, Abdul; Siratunnisak, Nadia (AcTion: Aceh Nutrition Journal, 2016)
The instant beverage product ingredients bran is a powder made from rice bran with the addition of sugar, saffron and cocoa powder. The addition of the cocoa powder bran instant drinks can enhance the flavor of drinks, so the demand by the public and boost the selling price of rice bran. This study is experimental by using bran as the manufacture of beverages physical, chemical and organoleptic. The experimental design used was completely randomized design (CRD) with 4 treatments with 3 repetitions. Based on the physical properties of rice bran instant drink water content showed that the more the addition of cocoa powder the higher the water content, pH is highest in treatment T3 (BC 250, BK 250), while the ash content is highest in the control treatment. Based on the organoleptic test of the instant beverage bran with the addition of 350, 300, 250 grams of cocoa powder to the acceptability of flavor, color, aroma and texture result of variance (ANOVA) significantly affect the taste, aroma, color, texture in instant drinks bran. The impact of the addition of cocoa powder in instant drinks bran to the taste, aroma, levels of protein, fiber, starch, pH, moisture content and ash content with a variety of treatments (T0, T1, T2, and T3).Â Keywords:Â  Rice bran, cocoa powder, physical and chemical properties